WMAP 5-year constraints on time variation of α and m_e in a detailed recombination scenario - Scoccola, Claudia Graciela (2008)
We study the role of fundamental constants in an updated recombination scenario. We focus on the time variation of the fine structure constant α, and the electron mass me in the early Universe, and put bounds on these quantities by using data from CMB including WMAP 5-yr release and the 2dFGRS power spectrum. We analyze how the constraints are modified when changing the recombination scenario. PG 1159 evolutionary models with stellar masses ranging from 0.530 to 0.741 M which take into account the complete evolution of progenitor stars. Results. We conclude that asteroseismology is a precise and powerful technique which determines the masses to a high internal accuracy, but it depends on the adopted mass determination method. In particular, we find that in the case of pulsating PG 1159 stars characterized by short pulsation periods, such as PG 2131+066 and PG 0122+200, the employment of the asymptotic period spacings overestimates the stellar mass by about 0.06 M as compared with inferences from the average of the period spacings. In this case, the discrepancy between asteroseismological and spectroscopical masses is markedly reduced when use is made of the mean period spacing ∆Π instead of the asymptotic period spacing ∆Πa .